The use of lignin in the rheological modification of Dura asphalt - saad alzbaidy; Ammar Al-Khazraji (College of Education for Pure Sciences, 2020)
This study was included treatment of the Dura asphalt with lignin as a natural polymeric additive and air blowing with three paths. The first path: the rheological properties of the asphalt were modified by adding the lignin to the asphalt and in various proportions in the presence of anhydrous aluminum chloride as a catalyst for this process at the optimum conditions for the catalytic oxidation process that was identified which is 150 centigrade and a time of 60 min. The second path : the rheological properties of the asphalt were modified using the use of lignin as an additive and with the presence of 1% sulfur(by weight)at a time of 60 minutes and a temperature of 180 ° C which is the optimal conditions for the non-catalytic air blowing process that was identified. As for the third track, the lignin was treated with asphalt without the use of anhydrous aluminum chloride under optimal conditions for the non-catalytic process. The study showed asphalt with completely different rheological properties compared to the original asphalt, which represents the primary goal behind the continuous quest for altering the rheological specifications of the original asphalt in a way that is compatible with the nature of use in different and specific fields, some samples can be using in paving as in samples(,AS19,AS20 ,AS50).As well as a moisture inhibitor and flattening as in samples(AS22,AS40,AS41 ,AS51, AS52).The use of asphalt in various fields is determined depending on the measurements made, ductility ,softening point,penetration,asphaltenes percentage,penetration index,aging test,marshall test .